1995
DOI: 10.1001/jama.1995.03520430057039
|View full text |Cite
|
Sign up to set email alerts
|

Medical Migration and the Physician Workforce

Abstract: In recent years, participation of IMGs in GME and practice has increased significantly. Most IMGs in GME are not exchange visitors, but are either permanent residents or US citizens. Patterns of specialization and location of IMGs ultimately mirror those of USMGs. National IMG policy must be examined in light of the projected surplus of physicians in the United States. The best option for long-term control of the number of physicians in practice, USMG or IMG, is a system of specifying the number of GME positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Research conducted in other countries reflect similar difficulties in regard to costs, an influx of physicians in the training country, and difficulties maintaining a balance between the needs of both the training and source countries [21, 22]. For example, a study from the USA reported that a significant proportion of visa trainees ultimately entered into permanent practice in the country, which is contrary to the original purpose of the visa exchange program [23]. The United Kingdom changed regulations for Medical Training Initiative visa holders, requiring them to leave the United Kingdom at the end of their training and to spend a minimum of 12 months outside the country before applying for a work permit to return to the United Kingdom [22].…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted in other countries reflect similar difficulties in regard to costs, an influx of physicians in the training country, and difficulties maintaining a balance between the needs of both the training and source countries [21, 22]. For example, a study from the USA reported that a significant proportion of visa trainees ultimately entered into permanent practice in the country, which is contrary to the original purpose of the visa exchange program [23]. The United Kingdom changed regulations for Medical Training Initiative visa holders, requiring them to leave the United Kingdom at the end of their training and to spend a minimum of 12 months outside the country before applying for a work permit to return to the United Kingdom [22].…”
Section: Discussionmentioning
confidence: 99%
“…An examination of the American Medical Association Masterfile reveals that during the period between 1981 and 2001, almost 125,000 IMGs entered the U.S. medical workforce (Mullan, Politzer, and Davis 1995; AMA 1996; Lohr, Vanselow, and Detmer 1996; Mullan 1996, 1997; Cooper 2003). North Carolina has experienced a similar influx of IMGs.…”
mentioning
confidence: 99%
“…In the United States, every year there are at least 5,000 more openings for first year residency trainees than there are graduates of U.S. medical schools (Barzanzky and Etzel 2005; Brotherton, Rockey, and Etzel 2005). Many of these training slots filled by IMGs are in teaching hospitals in large urban areas that have traditionally served large numbers of minorities, uninsured, and low‐income patients (Mullan, Politzer, and Davis 1995).…”
mentioning
confidence: 99%
See 2 more Smart Citations